A new species of the genus Nidilaelaps Shaw (Acari: Mesostigmata: Laelapidae) from Cuba - Omid Joharchi; Sergey G. Ermilov (Persian Journal of Acarology)
We present the first record of Nidilaelaps Shaw in the Caribbean area on the basis of a new species, Nidilaelaps cubaensis sp. nov., collected from forest litter in Cuba. The new species is described and illustrated based on morphological characters of the adult female and compared with closely related species.